Implementation of Teaching Campus 6 to Improve Literacy and Numeracy of SDN 1 Mataram Students: Implementasi Kampus Mengajar 6 untuk Meningkatkan Literasi dan Numerasi Siswa SDN 1 Mataram - Retna Ayu Rachmawati; Rifa Aulia; Fitra Rizki Ramdhani; Ismail Febri Adikusuma; Azziadati Azziadati (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
This community service program through the Kampus Mengajar Batch 6 at SDN 1 Mataram aims to improve students’ literacy and numeracy skills by implementing contextual and participatory activities. The program was developed in response to low national literacy and numeracy scores among primary school students. This initiative involved university students collaborating with the school community to design and conduct various engaging learning activities. The methods used followed a descriptive-participatory approach based on Community-Based Service Learning (CBSL), focusing on real problems, collaboration, and sustainability. Key activities included Literacy-Numeracy Games, Reading Corner, KUBACADA (Reading at the Library), and Learning Out of Class (LOOCs) such as tie-dye making and planting. These interventions were observed to increase student motivation, engagement, and conceptual understanding. The results showed a significant improvement in students’ post-test scores, supported by positive responses from teachers and the school principal. This program demonstrates the effectiveness of student–school partnerships in creating meaningful learning experiences and promoting literacy and numeracy culture in schools. The approach is practical, cost-effective, and replicable, offering valuable insights for future educational programs aiming to strengthen foundational skills in Indonesian primary schools.